¿Qué es la gamificación después de todo? - Alves Pereira, Jocimario (2025)
Gamification is a process that has been the subject of debate in the 21st century. A particularly delicate topic is the erroneous concepts related to ludic, games, and gamification. Despite having a single “gen”, it is possible to separate them, mainly thinking about the objectives and their application in education, for example. Considering that, this essay seeks to clarify the conceptual limits of gamification and its relation with the ludic and the game, exploring concepts and approaches. In this way, we expect to contribute to combating the dubious vision of gamification. Thus, without relegating other investigations, we assure that the objective of the ludic is to entertain (play), the game is to compete and the gamification is to involve through a process that uses game elements other than in games.